Data analysis of malnutrition in India: a review of numerous factors - Chakravorty, Sukanya; Manisha, (International Journal Of Community Medicine And Public Health, 2023)
Malnutrition is one of the most critical areas which needs government focus as it plays a crucial role in a country's economic and social development. In recent times, India is proving to be one of the fastest-growing countries in the South Asian region. Malnutrition and hunger rate is reduced to achieve The United Nation's second Sustainable Development Goal, Zero Hunger, to end world hunger by 2030. However, some states of India still serve as home to a more significant number of stunted and underweight children, especially in Bihar and Meghalaya, respectively. (NFHS-5) The current paper focuses on data analysis of malnutrition in India including several factors based on the qualitative research method. A systematic study was done to collect data by reviewing thousands of national- international journals and reports of 3rd, 4th and 5th NFHS and Globally hunger index of India, and WHO report on malnutrition in India. The government of India took the step of launching Poshan Abhiyan in 2017, which needs to be more focused on ruler areas of India.